A new complex mental health test in a positive psychological framework - Zábó, Virág; Oláh, Attila; Vargha, András (Frontiers in Psychology, 2022)
According to the Maintainable Positive Mental Health Theory (MPMHT), the main pillars of positive mental health are global well-being, efficient coping that enables an individual to maintain positive conditions and functioning, savoring capacity, resilience, and dynamic self-regulation. This study presents the validation of a new five-scale mental health test, the Mental Health Test (MHT) that operationalizes MPMHT. The methodology comprised two online cross-sectional studies using self-report questionnaires. Participants in Study I (n = 1,736; 448 males, 1,288 females; mean age 51.3 years; SD = 11.6 years) filled in the MHT, the Flow, the PERMA Questionnaire (PERMA-Profiler), and the Flourishing Scale. Participants in Study II (n = 1,083; 233 males, 847 females; mean age 33.9 years; SD = 12.2 years) filled in the MHT, the Shortened Aspiration Index, the short form of the Beck Depression Inventory, the WHO Well-Being Index, the Satisfaction with Life Scale, the Purpose in Life Test, and the Schema Questionnaire–Short Form. Exploratory factor analysis identified a five-factor structure with 17 items in Study I that was confirmed with excellent fit measures in confirmatory factor analysis in Study II. Both studies indicated a high level of internal consistency (above .70). In each subscale, a minimum part of 44% did not overlap with the set of the other subscales. The content validity of the subscales was confirmed by 10 tests of mental health. We found a positive correlation of the self-regulation and resilience subscales with age, while women showed a higher level of savoring than men at all age levels. When Study I was replicated after two weeks and again after 11 months, excellent internal consistency and good test–retest correlation values of the MHT scales were found. The MHT can thus be considered a reliable and valid measurement tool for mental health.